2006
DOI: 10.1083/jcb.200606113
|View full text |Cite|
|
Sign up to set email alerts
|

Did2 coordinates Vps4-mediated dissociation of ESCRT-III from endosomes

Abstract: The sorting of transmembrane cargo proteins into the lumenal vesicles of multivesicular bodies (MVBs) depends on the recruitment of endosomal sorting complexes required for transport (ESCRTs) to the cytosolic face of endosomal membranes. The subsequent dissociation of ESCRT complexes from endosomes requires Vps4, a member of the AAA family of adenosine triphosphatases. We show that Did2 directs Vps4 activity to the dissociation of ESCRT-III but has no role in the dissociation of ESCRT-I or -II. Surprisingly, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
186
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(209 citation statements)
references
References 21 publications
20
186
1
2
Order By: Relevance
“…Our mutational and NMR spectroscopic data are consistent with a model in which the terminal helix of CHMP1B makes a MIM1-like interaction with the helix 2/3 groove of the first LIP5 MIT module. CHMP1B/Did2p is an unusual ESCRT-III protein in that it binds well to the MIT domains from both VPS4 and LIP5 (33,34,39,40,50,58). This is apparently possible because the helix 2/3 grooves of the MIT domains from VPS4 and LIP5 are similar in character.…”
Section: Discussionmentioning
confidence: 99%
“…Our mutational and NMR spectroscopic data are consistent with a model in which the terminal helix of CHMP1B makes a MIM1-like interaction with the helix 2/3 groove of the first LIP5 MIT module. CHMP1B/Did2p is an unusual ESCRT-III protein in that it binds well to the MIT domains from both VPS4 and LIP5 (33,34,39,40,50,58). This is apparently possible because the helix 2/3 grooves of the MIT domains from VPS4 and LIP5 are similar in character.…”
Section: Discussionmentioning
confidence: 99%
“…28,36 This result suggests that Vps4 activity is necessary for cargo transport and for removal of the ESCRT machinery from the endosomal membrane. However, even though dissociation of ESCRT-III is essential for sorting, it is not a prerequisite for luminal vesicle formation, 37 and for uncoupling MVB cargo sorting from the budding of vesicles into the endosomal lumen.…”
Section: Biogenesis Of Mvbsmentioning
confidence: 99%
“…Establishment of an in Vitro Biochemical Assay System for MVB Formation-In previous MVB studies, internal vesicles in the endosomes have been observed by electron microscopy (EM) (15,38). However, quantification of MVB formation by EM analysis is limited.…”
Section: Endosomal Na ϩ /H ϩ Exchange Activity Is Required For Efficimentioning
confidence: 99%